2019
DOI: 10.1007/s00344-018-09912-7
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Calcium Oxalate Crystals and Distribution of Arabinogalactan Proteins (AGPs) in Ovary Cells During Fragaria x ananassa (Duch.) Development

Abstract: In this study, the presence of calcium oxalate crystals and distribution of arabinogalactan proteins (AGPs) in the ovary of Fragaria x ananassa (Duchesne) were investigated. The arrangement of the AGP epitopes was analyzed using immunohistochemistry techniques with JIM13, JIM15, and MAC207 monoclonal antibodies. To confirm the immunofluorescence studies, experiments at the subcellular level were performed with the immunogold method using transmission electron microscopy. We observed calcium oxalate crystals as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…According to Leszczuk et al [ 42 ], AGPs are involved in establishment of the cell wall, namely the plasma membrane continuum. During maturation in Pilosella and Taraxacum , mucilage cells undergo an intense period of secretory activity, which leads to dramatic cytological changes in the relationship between the cell wall and the plasma membrane [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Leszczuk et al [ 42 ], AGPs are involved in establishment of the cell wall, namely the plasma membrane continuum. During maturation in Pilosella and Taraxacum , mucilage cells undergo an intense period of secretory activity, which leads to dramatic cytological changes in the relationship between the cell wall and the plasma membrane [ 31 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leszczuk et al [ 42 ] showed the presence of AGPs labeled with JIM13 and JIM15 in close proximity to calcium oxalate (CaOx) crystals in the ovary wall of Fragaria × ananassa (Rosaceae). These authors were successful in performing an immunogold reaction, which confirmed the presence of AGPs at the edge of the CaOx crystals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calreticulin affects intracellular Ca 2+ homoeostasis by modulation of endoplasmic reticulum Ca 2+ storage and transport (Michalak et al ., 1999; Nakata et al ., 2003). Recently it was found that CaOx crystals in ovary cells are associated with arabinogalactan proteins that could act as calcium binding and storage molecules (Leszczuk et al ., 2019). Moreover several substances accumulate within the vacuoles of crystal cells, some of them with strong Ca‐binding capacity.…”
Section: Occurrence Of Ccais Must Be Considered On a Holistic Basismentioning
confidence: 99%